2019
DOI: 10.1038/s41564-019-0514-6
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary compaction and adaptation visualized by the structure of the dormant microsporidian ribosome

Abstract: Microsporidia are eukaryotic parasites that infect essentially all animal species, including many of agricultural importance 1-3 , and are significant opportunistic parasites of humans 4. They are characterized by having a specialized infection apparatus, an obligate intracellular lifestyle 5 , rudimentary mitochondria and the smallest known eukaryotic genomes 5-7. Extreme genome compaction led to minimal gene sizes affecting even conserved ancient complexes such as the ribosome 8-10. In the present study, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
148
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(157 citation statements)
references
References 42 publications
9
148
0
Order By: Relevance
“…Microsporidia also have reduced noncoding RNAs, including the 18s RNA, which is only approximately 2/3 as large as in other eukaryotes and results in the smallest eukaryotic ribosomes [13]. Although this reduction has led to several binding sites being eliminated, structural and mass spectrometry analysis of ribosomes from Vairimorpha necatrix demonstrated that most conserved ribosomal proteins can still bind [14]. Microsporidia also have reduced organelles, including mitochondrial remnants known as mitosomes [15].…”
Section: What Do Microsporidia Have In Common?mentioning
confidence: 99%
See 2 more Smart Citations
“…Microsporidia also have reduced noncoding RNAs, including the 18s RNA, which is only approximately 2/3 as large as in other eukaryotes and results in the smallest eukaryotic ribosomes [13]. Although this reduction has led to several binding sites being eliminated, structural and mass spectrometry analysis of ribosomes from Vairimorpha necatrix demonstrated that most conserved ribosomal proteins can still bind [14]. Microsporidia also have reduced organelles, including mitochondrial remnants known as mitosomes [15].…”
Section: What Do Microsporidia Have In Common?mentioning
confidence: 99%
“…The use of ancestral gene reconstruction has revealed how nucleotide transporter genes evolved [16]. Proteomic technologies such as mass spectrometry have been used to study the localization of microsporidia proteins as well as their translational fidelity [12,14,19]. Cryoelectron microscopy has been used to determine the structures of microsporidia ribosomes.…”
Section: Future Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…An important example of divergence among eukaryotes is the kinetoplastid family, which has been the object of several structural studies [ 21 , 22 , 23 , 24 ], showing ribosomes with fragmented rRNA’s that are comparable in size to prokaryotic counterparts, with nearly all the eukaryote-specific rRNA expansion segments missing. Similarly, during their evolution into organisms with highly compacted genomes, microsporidia have removed essentially all eukaryotic expansion segments and repurposed several ribosomal proteins to compensate for the extensive rRNA reduction [ 25 ]. On the prokaryotic side, bacteria with short genomes also commonly show a reduction of rRNA variation with loss of specific ribosomal proteins [ 26 ], suggesting some future work to visualize and confirm these changes through 3D structures.…”
Section: The Multiple Sources Of Heterogeneity In Ribosome Structumentioning
confidence: 99%
“…While the structure of the ribosomes is well conserved, structural features of ribosomes may vary significantly between different species, suggesting species-specific adaptations of protein synthesis (Ahmed et al ., 2016; Ahmed et al ., 2017; Barandun et al ., 2019; Bieri et al ., 2017; Kushwaha and Bhushan, 2020; Eyal et al ., 2015; Greber and Ban, 2016; Melnikov et al ., 2012; Melnikov et al ., 2018). For example, structural analysis of mycobacterial ribosome revealed that the 30S ribosomal subunit lacks the protein bS21 that is found in Escherichia coli .…”
Section: Introductionmentioning
confidence: 99%